2013
DOI: 10.1074/jbc.m113.449942
|View full text |Cite
|
Sign up to set email alerts
|

Real-time Kinetics of High-mobility Group Box 1 (HMGB1) Oxidation in Extracellular Fluids Studied by in Situ Protein NMR Spectroscopy

Abstract: Background: Redox of extracellular HMGB1 protein plays an important role in inflammation. Results: The half-life of all-thiol HMGB1 was ϳ17 min in serum and saliva and significantly longer in cancer cell culture medium and was modulated by exogenous ligands (e.g. heparin). Conclusion:The extracellular environment dictates HMGB1 oxidation kinetics. Significance: Our approach permits investigating protein oxidation in situ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
63
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 46 publications
(55 reference statements)
2
63
1
Order By: Relevance
“…Thus, fr-HMGB1 may be susceptible to ROS-mediated oxidation and conversion to ds-HMGB1 in vivo. Indeed, fr-HMGB1 has a relatively short half-life (∼17 min) in biological fluids such as serum and saliva [37]. Other studies support this hypothesis and our findings are in agreement with these investigations [6, 16, 32, 38].…”
Section: Discussionsupporting
confidence: 83%
“…Thus, fr-HMGB1 may be susceptible to ROS-mediated oxidation and conversion to ds-HMGB1 in vivo. Indeed, fr-HMGB1 has a relatively short half-life (∼17 min) in biological fluids such as serum and saliva [37]. Other studies support this hypothesis and our findings are in agreement with these investigations [6, 16, 32, 38].…”
Section: Discussionsupporting
confidence: 83%
“…15,35 It has been shown recently that in the extracellular space HMGB1 is oxidized quickly: the half-life for allthiol HMGB1 within the serum is 17 minutes before it is oxidized into disulfide HMGB1 in vitro. 57 In addition, in a model of ischemic stroke mainly all-thiol HMGB1 is found after 2 hours in serum samples, whereas both all-thiol and disulfide HMGB1 are found after 24 hours. 32 Therefore, reduced HMGB1 released from platelets is probably oxidized quickly within the blood stream.…”
Section: Discussionmentioning
confidence: 99%
“…Disulfide HMGB1 can only act on the receptor toll-like receptor 4 (TLR4) (110) and influences the production of inflammatory cytokines (133)(134)(135). Important work using an NMR-based approach to distinguish the oxidation states and half-lives of HMGB1 in serum, saliva and cell culture media revealed that the half-life of all-thiol HMGB1 is as short as 17-18 minutes in human serum and saliva and the subsequent clearance of the disulfide HMGB1 varies between 65 and 642 minutes, depending on the extracellular fluid (139) (Fig. 3).…”
Section: Extracellular Forms Of Hmgb1mentioning
confidence: 99%
“…3). Disulfide HMGB1 is then further reduced following oxidation of Cys-106 in the B-domain to an inert form (139). …”
Section: Extracellular Forms Of Hmgb1mentioning
confidence: 99%
See 1 more Smart Citation